PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS DIGITAL MENGGUNAKAN MODEL PROJECT BASED LEARNING - Wan Nurul Atikah Nasution; Eva Mizkat; Ainul Husna; Eva Margaretha Saragih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to (1) describe the process of developing digital-based learning media using the Project-Based Learning Model. 2) describe the results of the digital-based learning media. The resulting products are: (1) Digital-based Indonesian Language Learning Media. This research resulted in a product in the form of digital-based learning media developed by Indonesian Language and Literature Education students in the Learning Media course. This research method used R&D (Research and Development) structured using the ADDIE learning development model with five development stages: Analysis, Design, Development, Implementation, and Evaluation. The products developed by 25 students were: 3 students used Google Slides, 6 students used Canva Video, 4 students used Google Forms, 5 students used Quizizz, 5 students used PowerPoint (1 video and 4 slides), 1 student used Flipbook, and 1 student used Educaplay. Keywords: Learning Media Development, Project-Based Learning, Digital Media Abstrak: Penelitian ini bertujuan untuk (1) Untuk mendeskripsikan proses pengembangkan media pembelajaran berbasis digital menggunakan Model  Project Based Learning. 2) Untuk mendeskripsikan hasil media pembelajaran berbasis digital. Produk yang dihasilkan adalah: (1) Media Pembelajaran Bahasa Indonesia berbasis digital. Penelitian ini menghasilkan produk berupa media pembelajaran berbasis digital yang dikembangkan mahasiswa Pendidikan Bahasa dan Sastra Indonesia pada mata kuliah Media Pembelajaran. Metode penelitian ini menggunakan R&D (Researh and Development) disusun dengan menggunakan model pengembangan pembelajaran ADDIE dengan 5 tahapan pengembangan yaitu Analysis, Design, Development, Implementation, dan Evaluation. Hasil produk yang dikembangkan oleh 25 mahasiswa yakni: terdapat 3 orang mahasiswa menggunakan aplikasi Google Slide, 6 orang menggunakan Video Canva, 4 orang menggunakan aplikasi Google form, 5 orang mahasiswa menggunakan aplikasi Quizizz, 5 orang menggunakan aplikasi Powerpoint (1 video dan 4 slide), 1 orang menggunakan aplikasi Flipbook, 1 orang menggunakan aplikasi Educaplay. Kata kunci: Pengembangan Media Pembelajaran, Project Based Learning, Media  Digital